Causality among CO2 emissions, energy consumption and economic growth in Italy. (18th May 2019) - Stamatiou, Pavlos; Dritsakis, Nikolaos
The aim of this paper is to investigate the relationship between CO2 emissions (carbon dioxide emissions), energy consumption and economic growth in Italy, using annual data covering the period 1960-2011. The unit root tests results indicated that the variables are not stationary in levels but in their first differences. Subsequently, the Johansen cointegration test showed that there is a cointegrated vector between the examined variables. The vector error correction model (VECM) is used in order to find the causality relations among the variables. The empirical results of the study revealed that both in the short and long run there is a strong unidirectional causality relation between economic growth and CO2 emissions with direction from economic growth to CO2 emissions. Finally, the impulse response functions indicated that a reduction in CO2 emissions has a positive effect on energy consumption, while it causes a decrease in economic growth.